ANALYSIS OF FAMILY ECONOMIC EDUCATION AND FINANCIAL MANAGEMENT (STUDIES ON HUSBAND WHICH MARRIED WORKER INDONESIAN IMMIGRANTS IN SUMBERMANJING WETAN DISTRICT) - Maulidia, Fadlilatul; Rokhmani, Lisa (Universitas Pasundan, 2025)
Based on data from BP2MI (2024), Indonesian Migrant Workers (PMI) are predominantly women, comprising 68% of the total. This gender composition has led to a shift in traditional family structures, particularly through the exchange of roles, where wives work abroad while husbands take on domestic responsibilities. This creates a new dynamic in the household with dual and reversed gender roles.This study focuses on husbands of Indonesian migrant workers who have assumed the role of economic educators and financial managers in the family, especially concerning their children's welfare. The research was conducted in Sumbermanjing Wetan District, Malang Regency, with a qualitative method using a phenomenological approach.The study explores several key areas: the family's economic condition, the internalization of economic education in daily life, the husband’s financial management practices, and the perceived impact of this education on children. Findings show that the families' economic conditions are generally unstable and heavily reliant on remittances from the wives. Economic education internalized within the household includes lessons on saving, managing pocket money independently, and practicing wise and frugal consumption—positively influencing the children’s behavior. However, the study reveals that financial management lacks a structured foundation. There is little evidence of proper financial planning, control, utilization, or evaluation. As a result, despite the positive efforts in informal financial education, the overall family financial system remains vulnerable and unsustainable in the long term.